Influence of various physical factors upon the radiative equilibrium of the atmosphere - GODBOLE , R. V.; KELKAR, R. R. (MAUSAM, 1971)
The effects of given variations in water vapour, carbon dioxide, and ozone Upon the radiative equilibrium of the atmosphere have been investigated. The equilibrium temperature has been computed as an asymptotic steady state by marching process. The study has shown that water vapour can alone account for 96.7 per cent of the temperature distribution of the troposphere, whereas ozone together with carbon dioxide can practically account for the temperature distribution of the stratosphere. Ozone is the only gas responsible for maintaining warm stratosphere. The surface albedo and hence the ground temperature plays a very important role in fixing the temperature distribution of the vertical column.